2018
DOI: 10.3390/molecules23051186
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis in Chinese Cabbage (Brassica rapa ssp. pekinensis) Provides the Role of Glucosinolate Metabolism in Response to Drought Stress

Abstract: Although drought stress is one of the most limiting factors in growth and production of Chinese cabbage (Brassica rapa L. ssp. pekinensis), the underlying biochemical and molecular causes are poorly understood. In the present study, to address the mechanisms underlying the drought responses, we analyzed the transcriptome profile of Chinese cabbage grown under drought conditions. Drought stress transcriptionally activated several transcription factor genes, including AP2/ERFs, bHLHs, NACs and bZIPs, and was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 61 publications
(66 reference statements)
1
35
0
Order By: Relevance
“…Although most of the altered responses represent a dampened stress response due to the increased drought tolerance of dgs1-1 plants, a small set of genes involved in sulfur metabolism and glucosinolate biosynthesis was mis-expressed in these lines ( Figure 7B). Upregulation of glucosinolate biosynthesis and metabolism has been linked to responses to drought stress (Eom et al, 2018). A positive regulator of glucosinolate metabolism in Arabidopsis, MYB29, has been previously shown to be a negative regulator of AOX expression (Zhang et al, 2017), and this may account for the reduction of AOX observed in the dgs1-1 lines ( Figure 5A).…”
Section: Discussionmentioning
confidence: 97%
“…Although most of the altered responses represent a dampened stress response due to the increased drought tolerance of dgs1-1 plants, a small set of genes involved in sulfur metabolism and glucosinolate biosynthesis was mis-expressed in these lines ( Figure 7B). Upregulation of glucosinolate biosynthesis and metabolism has been linked to responses to drought stress (Eom et al, 2018). A positive regulator of glucosinolate metabolism in Arabidopsis, MYB29, has been previously shown to be a negative regulator of AOX expression (Zhang et al, 2017), and this may account for the reduction of AOX observed in the dgs1-1 lines ( Figure 5A).…”
Section: Discussionmentioning
confidence: 97%
“…RNA-seq data from drought-treated tomato leaf samples were obtained from the National Agricultural Biotechnology Information Center (NABIC, http://nabic.rda.go.kr) with accession number NN-5505 [21]. Then, the quality of the raw data was controlled by using the FastQC tool and Trimmomatic v.0.33 as described by Eom et al [5]. The clean reads were mapped to the tomato reference sequence (Tomato Genome version SL3.0 and Annotation ITAG3.10, https://solgenomics.net/ organism/Solanum_lycopersicum/genome), using the HISAT2 aligner (http://ccb.jhu.edu/software/ hisat2/index.shtml ).…”
Section: Transcriptome Data and Transcriptome Assemblymentioning
confidence: 99%
“…Droughts led to global cereal (maize, rice, and wheat) production deficits of 10.1% on average during the past four decades [4]. Under drought conditions, crops display various physiological and biochemical responses, including stomatal movement (the opening or closing of stomata), morphological changes (repression of cell growth and development),and alteration in biosynthetic pathways, antioxidant pathways, and respiration pathways; all of these aid survival in this unfavorable climate [5]. Understanding drought-induced molecular and physiological mechanisms is necessary for successful yield protection in the context of drought.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze the expression patterns of BraNIN genes, we used RNA-seq data of drought treated-Chinese cabbage [22]. L1 (R1), L2 (R2) and L3 (R3) indicated leaf (root) samples obtained from Stage 1 (nonstressed condition), Stage 2 (soil water content of 20%) and Stage 3 (soil water content of 5%) plants, respectively.…”
Section: Expression Analysis Of Braninsmentioning
confidence: 99%
“…L1 (R1), L2 (R2) and L3 (R3) indicated leaf (root) samples obtained from Stage 1 (nonstressed condition), Stage 2 (soil water content of 20%) and Stage 3 (soil water content of 5%) plants, respectively. Transcript levels were calculated using SAMtools (http://samtools.sourceforge.net/) and relative transcript abundances were analyzed using DEseq as described by Eom et al [22].…”
Section: Expression Analysis Of Braninsmentioning
confidence: 99%